ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. W G2P1A0 DENGAN RESIKO TINGGI ANEMIA KEHAMILAN DI WILAYAH KERJA PUSKESMAS BUMIAYU - Ade Yuni Andreani; Himatul Khoeroh (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
Based on data from the Indonesian Ministry of Health, the number of MMR in 2020 reached 4,627 people. This number increased by 10.25% compared to 2019 of 4,197 people. The number of infant deaths in 2019 was 26,000 cases and increased by almost 40% to 44,000 cases in 2020. The Bumiayu Health Center, one of the auspices of the Brebes Regency in Central Java, contributed 2 cases of AKI and 5 cases of IMR in 2020. by conducting comprehensive midwifery care with a continuity of care approach which is carried out starting from the mother during pregnancy to family planning. Researchers implemented comprehensive midwifery care for pregnant women, childbirth, newborns, postpartum, and family planning using Varney and SOAP documentation. The research method used is descriptive qualitative with a case study approach. Data collection uses interviews, observations, physical examinations, supporting examinations, documentation studies, and literature studies, as well as medical record documentation studies, the main informant is Mrs. W with 2 additional informants namely 1 coordinating midwife and 1 patient's family and 1 triangulation informant namely the head section of the brebes district health office. Based on the results of pregnancy, childbirth, newborns, postpartum, and family planning, there are problems in pregnancy, namely at 30+3 weeks of gestation with an Hb level of 10.4 g/dl in the category of mild anemia. There is no gap between theory and practice. From the results of the study, it can be concluded that comprehensive care for Mrs. W 25 years of gestation, psychological postpartum, physiological delivery, and physiological BBL. There is no gap between theory and practice.